Individualistic and collective causal knowledge structures for understanding sequential and emergent processes - Chi, Michelene T. H. (Frontiers in Education, 2023)
This paper presents a unifying account for why many biological, ecological, and environmental processes (such as the spread of Covid19) are particularly difficult for students to understand. The hypothesis is that students bring the perspective of “Individualistic causal thinking” for understanding these processes, instead of “Collective causal thinking,” resulting in misunderstanding. This paper will: describe a framework called PAIR-C for defining both kinds of causal knowledge structures; explain how this definitional framework was developed inductively from the massive amount of data available on students’ misconceptions; show how such a framework is needed to understand many phenomena in biology and other domains; and suggest how this framework can be translated into instruction to improve students’ understanding.